2004
DOI: 10.1097/01.ta.0000149497.20065.f4
|View full text |Cite
|
Sign up to set email alerts
|

Non-Helmeted Motorcyclists: A Burden to Society? A Study Using the National Trauma Data Bank

Abstract: Non-helmeted motorcyclists have worse outcomes than their helmeted counterparts independent of the use of alcohol or drugs. Furthermore, they monopolize more hospital resources, incur higher hospital charges, and as non-helmeted motorcyclists frequently do not have insurance, reimbursement in this group of patients is poor. Thus, the burden of caring for these patients is transmitted to society as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 20 publications
1
36
1
3
Order By: Relevance
“…It was reported that none of the patients who used safety helmet died in hospital compared to 3% of those who had not worn helmet or seat-belt. Higher hospital charges and longer length of hospitalization were reported due to not using safety facilities (27)(28)(29)(30). Seatbelt legislation was passed in Iran in 2005 and Soori et al (4), showed that mandatory seatbelt legislation reduced the number of RTIs in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that none of the patients who used safety helmet died in hospital compared to 3% of those who had not worn helmet or seat-belt. Higher hospital charges and longer length of hospitalization were reported due to not using safety facilities (27)(28)(29)(30). Seatbelt legislation was passed in Iran in 2005 and Soori et al (4), showed that mandatory seatbelt legislation reduced the number of RTIs in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Other situations from gun control to motorcycle helmet laws also exemplify this principle; in the case of the latter, helmet laws in many locations have been repealed following protests by riders who argue that to take away this freedom represents an infringement of personal rights. Overlooked, however, are statistics on the astounding cost to local society that a single head-trauma patient causes (requiring a recovery time of months or even years) following a motorcycle crash (Hundley et al, 2004). Now consider another aspect of a motorcycle-or for this matter, car, bus, truck, coal-fired power plant, or any greenhouse emitting activity.…”
Section: Introduction: the Public Health Context: Individual Rights Vmentioning
confidence: 98%
“…Çalışmamızda motosiklet kazalarında alkollü motor kullanma oranı %27.52 iken, kas iskelet sistemi yaralanması olan motosiklet kazalarında bu oran %32.7 idi. Bu oran Stutts [5] ve Hundley'in [23] çalışmasında %2-4 arasında olduğu görülmektedir. Bölgemizdeki alkol tüketiminin yüksek olmasının, alkol nedenli kazaların ve yaralanmaların oranını ve şiddetini arttırdığı düşünülmektedir.…”
Section: Discussionunclassified